Influence of Multifrequency Ultrasound-Assisted Freezing on the Flavour Attributes and Myofibrillar Protein Characteristics of Cultured Large Yellow Croaker (Larimichthys crocea) - Ma, Xuan; Yang, Dazhang; Qiu, Weiqiang; Mei, Jun; Xie, Jing (Frontiers in Nutrition, 2021)
The influence of multifrequency ultrasound-assisted freezing (UAF) as compared with single- and dual- UAF on the flavour, microstructure and myofibrillar proteins of cultured large yellow croaker was investigated in order to improve food quality in a sustainable way and address the major global challenges concerning food and nutrition security in the (near) future. Multifrequency UAF-treated samples had lower total volatile basic nitrogen values during freezing than single- and dual- UAF-treated samples. Thirty-six volatile compounds were identified by solid phase microextraction (SPME) coupled to gas chromatography–mass spectrometry (GC-MS) during freezing, and the multifrequency UAF-treated samples showed significant decreases in the relative contents of fishy flavoured compounds, including 1-penten-3-ol and 1-octen-3-ol. In addition, multifrequency UAF treatment better maintained a well-organized protein secondary structure by maintaining higher α-helical and β-sheet contents and stabilizing the tertiary structure. Scanning electron microscopy images indicated that the ice crystals developed by the multifrequency UAF were fine and uniformly distributed, resulting in less damage to the frozen large yellow croaker samples. Therefore, multifrequency UAF improved the flavour attributes and myofibrillar protein characteristics of the large yellow croaker samples. Overall, multifrequency ultrasound-assisted freezing can serve as an efficient way for improving food quality and nutritional profile in a sustainable way.